Simbolisme dalam Novel Jakarta Sebelum Pagi Karya Ziggy Zezsyazeoviennazabrizkie Kajian Semiotika Komunikasi - Wafiqotin Nazihah; Purwati Anggraini (TRANSFORMATIKA, 2019)
This Novel Jakarta Sebelum Pagi by Ziggy Zezsyazeoviennazabrizkie examines stories of love nuances which also contain socio-cultural elements in the modern era with a comparison of past stories to support the moral values presented. This study aims to examine abstract symbols so that multiple interpretations are made art connoisseurs. The author uses a type of qualitative research with a content analysis approach. Data was collected by grouping quotations between conversations between Abel's figure and other figures who shared similarity with symbolism in communication semiotics, namely symbolism of loyalty, trust, caring and habit. The results of the study which showed the discovery of four symbolism is as follows. First, the symbol of commitment is demonstrated by the blue Hyacinth flower that the character always brings to his lover. Second, trust is shown by pigs which are believed to have high ability to capture and intelligence, so that a symbol of a pig represents the character of Nissa (someone who can be trusted). Third, the concern is shown by grunts and growls by figures who cannot communicate using the five senses. Fourth, the custom symbol is illustrated by smoked pigs which are already polluted pollution in the city of Jakarta every day. The four symbols can be found in the discussion of imaginary novels.